Understanding the Determinants of Acute Otitis Media in Children Exposed to Tobacco Smoke: A Study from an Urban Indonesian Population - Ekananda, Nabilla Firya; Rusli, Christina; Anindya, Pramita (CoMPHI Journal: Community Medicine and Public Health of Indonesia Journal, 2025)
Tobacco smoking is a pervasive global health challenge, with its by-product, secondhand smoke, negatively impacting health, especially in vulnerable populations such as children. In Indonesia, ear disorders, notably Acute Otitis Media (AOM), are common pediatric morbidities. AOM, an inflammation of the middle ear, is frequently linked to high smoking activity and, critically, exposure to tobacco smoke. This study aimed to elucidate the association between secondhand smoke exposure and AOM occurrence in children aged 0-5 years presenting at Dr. Ramelan Naval Hospital, Surabaya. Utilizing a cross-sectional observational design, data were collected from 74 eligible pediatric patients through questionnaires detailing their smoke exposure and corresponding AOM diagnoses. Spearman's correlation analysis revealed a statistically significant relationship between secondhand smoke exposure and AOM incidence (p<0.001), characterized by a moderate correlation coefficient (r=0.329). The findings underscore that a significant proportion of pediatric AOM cases at our institution are associated with moderate secondhand smoke exposure. This research concludes that secondhand smoke exposure is a significant risk factor for Acute Otitis Media, particularly among children aged 0-5 years, highlighting a critical need for public health interventions to reduce household smoke exposure and improve pediatric ear health outcomes.